2016
DOI: 10.1155/2016/1084917
|View full text |Cite
|
Sign up to set email alerts
|

Subdiaphragmatic Renal Ectopia: Case Report and Review of the Literature

Abstract: Background. We report the case of a male infant whose right kidney migrated to an ectopic position after birth. The migration of a kidney in postnatal life without any symptoms has not been reported in literature so far. Case Presentation. In a series of antenatal and the first postnatal ultrasound scans, the right kidney was normally located within the right renal fossa. During the first 3 months of life, the kidney migrated to a subdiaphragmatic position. This was confirmed on MRI scan. The infant was asympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…Other scholars have postulated that an initial high cephalic origin of the renal germ results in congenital thoracic kidney[ 15 ]. An unusual case of kidney ascent in postnatal life has also been reported by Zolotas et al[ 16 ] in 2016. In this case, a male infant’s right kidney migrated gradually from the renal fossa to a higher position superior to the liver and below the diaphragm.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Other scholars have postulated that an initial high cephalic origin of the renal germ results in congenital thoracic kidney[ 15 ]. An unusual case of kidney ascent in postnatal life has also been reported by Zolotas et al[ 16 ] in 2016. In this case, a male infant’s right kidney migrated gradually from the renal fossa to a higher position superior to the liver and below the diaphragm.…”
Section: Discussionsupporting
confidence: 59%
“…Robotic laparoscopy has been successfully used in thoracorenal renal fixation many times and can be regarded as a replacement choice for laparotomy. Zolotas et al[ 16 ] suggested that the thoracic kidney associated with Bochdalek hernia should undergo surgery to avoid splanchnocele formation and strangulation. In our case, the aberrant kidneys did not impair renal function and further interventions were not required.…”
Section: Discussionmentioning
confidence: 99%
“…But if the diaphragm closes earlier, then the ascent will result in subdiaphragmatic kidney [1,16]. Postnatal cases of cephalad renal migration from infra-diaphragmatic location to both subdiaphragmatic and intrathoracic locations have been reported [17,18]. Most of the reported cases of subdiaphragmatic kidneys had normal renal function [9,12,17,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal cases of cephalad renal migration from infra-diaphragmatic location to both subdiaphragmatic and intrathoracic locations have been reported [17,18]. Most of the reported cases of subdiaphragmatic kidneys had normal renal function [9,12,17,19,20]. The chances of infection and its complications are less often seen in cephalad renal ectopia compared to caudal renal ectopia due to good drainage in cephalad renal ectopia [21] (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Wada stanowi następstwo zaburzonej migracji nerki z okolicy krzyżowej do okolicy lędźwiowej. Powstaje między 6. a 9. tygodniem embriogenezy [11,12]. W części przypadków jest uwarunkowana genetycznie.…”
Section: W St ę Punclassified